Using seafloor echo-integrated backscatter for monitoring single beam echosounder calibration - Le Bouffant, N.; Berger, L.; Fezzani, R. (Frontiers in Remote Sensing, 2025)
IntroductionIn recent years, methods have been developed to calibrate seafloor backscatter measurements from hydrographic multibeam echosounders. Some of these methods involve the use of well-characterized reference areas that consistently exhibit stable backscatter levels over the years. This study investigates the potential of measuring seafloor backscatter over such a known stable area with vertical single beam echosounders, to provide a straightforward monitoring of their calibration.MethodsWe propose a methodology for calculating standard seafloor surface backscattering at normal incidence, utilizing the standard volume backscattering echo-integration technique commonly used in fishery echosounders, which is also applicable to wideband frequency modulation (FM) transmissions. We explain how this technique compares to the typical multibeam echosounder computation, which is based on samples of maximum amplitude.ResultsThe operational accuracy of seafloor backscatter measurements taken over a known stable area is presented, with data collected over several years from various single-beam systems primarily calibrated using the sphere method.DiscussionThe repeatability of the results suggests that such natural seafloor reference areas can serve as a secondary calibration reference for quickly monitoring single-beam echosounders, through a straightforward acquisition and processing approach. While this method may not provide access to all the echosounder features controlled by sphere calibration, it can be used to adjust standard volume and surface backscattering measurements.